2010
DOI: 10.1073/pnas.1000133107
|View full text |Cite
|
Sign up to set email alerts
|

Natural hybridization generates mammalian lineage with species characteristics

Abstract: Most diploid species arise from single-species ancestors. Hybrid origins of new species are uncommon (except among polyploids) and are documented infrequently in animals. Examples of natural hybridization leading to speciation in mammals are exceedingly rare. Here, we show a Caribbean species of bat (Artibeus schwartzi) has a nuclear genome derived from two nonsister but congeneric species (A. jamaicensis and A. planirostris) and a mitochondrial genome that is from a third extinct or uncharacterized congener. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 57 publications
8
144
0
Order By: Relevance
“…Under particular circumstances hybridization upon secondary contact might actually lead to a novel evolutionary stable entity, as, for example, suggested for a number of animal taxa (Grant & Grant, 2002;Gompert et al, 2006;Larsen et al, 2010;, including other cichlid fishes (Salzburger et al, 2002). It has been shown that hybrid populations can rapidly generate novel (''transgressive'') phenotypes which might be rapidly sorted out via natural selection, or alternatively, that hybrid populations become isolated from their sources in particular habitats, to form a novel entity distinct from both parental species (Salzburger et al, 2002;Parsons et al, 2011).…”
Section: Taxonomic Considerationsmentioning
confidence: 99%
“…Under particular circumstances hybridization upon secondary contact might actually lead to a novel evolutionary stable entity, as, for example, suggested for a number of animal taxa (Grant & Grant, 2002;Gompert et al, 2006;Larsen et al, 2010;, including other cichlid fishes (Salzburger et al, 2002). It has been shown that hybrid populations can rapidly generate novel (''transgressive'') phenotypes which might be rapidly sorted out via natural selection, or alternatively, that hybrid populations become isolated from their sources in particular habitats, to form a novel entity distinct from both parental species (Salzburger et al, 2002;Parsons et al, 2011).…”
Section: Taxonomic Considerationsmentioning
confidence: 99%
“…G Nieto Feliner, I Álvarez, J Fuertes-Aguilar, M Heuertz, I Marques, F Moharrek, R Piñeiro, R Riina, JA Rosselló, PS Soltis and I Villa-Machío Heredity (2017) 118, 513-516;doi:10.1038/hdy.2017published online 15 March 2017 N atural hybridization and its role in evolution and specifically in generating new diversity is an old and yet endlessly revitalized topic (Lotsy, 1916;Anderson, 1949;Stebbins, 1959;Rieseberg et al, 2003;Mallet, 2007;Soltis and Soltis, 2009;Larsen et al, 2010;Arnold et al, 2012b;Pereira et al, 2014;Grant and Grant, 2015;Abbott et al, 2016;Pennisi, 2016). Homoploid hybrid speciation (HHS) is the formation of a newhybrid-species, independent from its parents, via hybridization with no whole-genome duplication and thus no increase in ploidy.…”
mentioning
confidence: 99%
“…I would also point out that examples of natural hybridization leading to speciation are exceedingly rare, especially in mammals Arnold et al, 1997 [13] . While most known cases of hybrid speciation occur in plants, the majority of documented cases involving animals have been observed in fish and insects Larsen et al, 2010 [26] . Perhaps most important in this discussion, mtDNA datasets have repeatedly shown to provide enough sufficient resolution for reconstructing a robust phylogeny and it also facilitates the molecular dating of divergence events within a phylogeny Krause et al, 2008 [27] .…”
Section: Discussionmentioning
confidence: 99%